2002
DOI: 10.1046/j.1523-1747.2002.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal Water Loss Does Not Correlate with Skin Barrier Function In Vitro

Abstract: The purpose of this study was to investigate the relationship between transepidermal water loss and skin permeability to tritiated water (3H2O) and the lipophilic penetrant sulfur mustard in vitro. No correlation was found between basal transepidermal water loss rates and the permeability of human epidermal membranes to 3H2O (p = 0.72) or sulfur mustard (p = 0.74). Similarly, there was no correlation between transepidermal water loss rates and the 3H2O permeability of full-thickness pig skin (p = 0.68). There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
3
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 28 publications
7
70
3
4
Order By: Relevance
“…In these studies, all the TEWL values were below the 5 g × m -2 × h -1 acceptance limit; moreover, freezing the skin did not necessarily result in a higher TEWL value (since TEWL values for frozen skin discs were both lower and higher than that for fresh skin from the same donor). The penetration of chemicals was also not dependent on the TEWL values measured, which is in line with the measured intact barrier function and the findings of others [8]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In these studies, all the TEWL values were below the 5 g × m -2 × h -1 acceptance limit; moreover, freezing the skin did not necessarily result in a higher TEWL value (since TEWL values for frozen skin discs were both lower and higher than that for fresh skin from the same donor). The penetration of chemicals was also not dependent on the TEWL values measured, which is in line with the measured intact barrier function and the findings of others [8]. …”
Section: Discussionsupporting
confidence: 91%
“…However, there are conflicting reports as to whether the freezing process affects the penetration of chemicals. The outcomes of the comparisons appear to depend on the physicochemical properties of chemicals tested [4,5,6,7], the skin tissues used (which vary between full-thickness [8], dermatomed [9,10] and isolated epidermis layers, i.e., 100 μm thick [11,12]), the length of storage (30-60 days [13] vs. a few hours [9]), and the parameters by which they were compared, e.g., distribution across skin layers, penetration coefficients and cumulative amounts in the receptor fluid (RF). Considering the varied reports of comparisons between fresh and frozen skin, before embarking on the main testing of 50 chemicals, we first evaluated whether the storage of human skin affected the penetration of model chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Gomaa et al [53] highlighted an earlier study by Chilcott's group [62] which suggested that TEWL cannot be used to predict transdermal delivery of drugs [63]. No correlation between TEWL and skin integrity was found, however this may be due to the use of different experimental protocols.…”
Section: Transepidermal Water Loss (Tewl) Monitoringmentioning
confidence: 99%
“…Podejrzewa się, że zmniejszenie nawilżenia skóry, a w rezultacie jej suchość, mogą być wywoła-ne przez hiperglikemię lub hiperosmolarność osocza, a nie utratę wody z naskórka w wyniku parowania [27,28]. Niezmieniony parametr TEWL w cukrzycy nie wyklucza innych defektów bariery naskórkowej i jak wskazują pojedyncze badania, korelacja między TEWL i prawidłową funkcją bariery naskórkowej jest kontrowersyjna i wymaga dalszych badań [29].…”
Section: Zmiany Biofizycznych Parametrów Skóry W Cukrzycyunclassified